2011
DOI: 10.4236/wja.2011.12006
|View full text |Cite
|
Sign up to set email alerts
|

Immunovirological and Biochemical Changes in Nigerian Patients with Hepatitis B Coinfection on Antiretroviral Therapy

Abstract: Hepatitis B virus (HBV) co-infection with HIV is high among Nigerians. Some studies have suggested impaired CD4 recovery among coinfected patients compared to the HIV mono infected. This retrospective study of treatment-naïve HIV infected patients was aimed at determining the trend of changes in CD4<sup>+</sup> counts, HIV-RNA and renal and liver function tests in response to combined antiretroviral therapy (CART). A questionnaire was utilised to extract clinical and laboratory data of HBV co infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
0
1
Order By: Relevance
“…According to this study renal function tests (urea, creatinine, uric acid) were not statistically significant among co and mono-infected HIV patients which supports the study conducted in Nigeria by Otegbayo et al who reported that serum urea and creatinine levels between HBV-HIV and HIV only infected patient were not statistically significant (p>0.05) [31].…”
supporting
confidence: 77%
“…According to this study renal function tests (urea, creatinine, uric acid) were not statistically significant among co and mono-infected HIV patients which supports the study conducted in Nigeria by Otegbayo et al who reported that serum urea and creatinine levels between HBV-HIV and HIV only infected patient were not statistically significant (p>0.05) [31].…”
supporting
confidence: 77%
“…Although the association between HCV positivity and CD4 count shows conflicting reports (Greub et al, 2000;Anderson et al, 2004;Hershow et al, 2005) It would appear that the immunological status of monoinfection is higher than HBV/HCVab coinfection, as evidenced by the higher CD4 counts in HIV monoinfected than HIV-coinfected with HBV/HCVab. Contrary to observations made Idoko et al in the North-central (Idoko et al, 2009) and Ortegbayo et al in South-western part of Nigeria (Otegbayo et al, 2011). The viral load was higher in HBV/HCVab than HIV monoinfected.…”
Section: Discussioncontrasting
confidence: 84%